2016
DOI: 10.1039/c6cp05254a
|View full text |Cite
|
Sign up to set email alerts
|

Near edge X-ray absorption mass spectrometry of gas phase proteins: the influence of protein size

Abstract: Multiply protonated peptides and proteins in the gas phase can respond to near edge X-ray absorption in three different ways: (i) non dissociative ionization and ionization accompanied by loss of small neutrals, both known to dominate for proteins with masses in the 10 kDa range. (ii) Formation of immonium ions, dominating for peptides in the 1 kDa range. (iii) Backbone scission leading to sequence ions which is typically weaker and has mainly been observed for peptides in the 1 kDa range. We have studied carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(72 citation statements)
references
References 31 publications
6
64
1
Order By: Relevance
“…We attribute the main ones to internal fragments formed by at least two backbone cleavages (see figure 3a). This is in line with our previously reported mass spectra of peptides after X-ray single photon absorption: we showed that peptides of similar size or smaller undergo extensive fragmentation into low-mass ions due to one or two bond cleavages 12,20 .…”
Section: Photoabsorption Mass Spectra Of Peptide Monomerssupporting
confidence: 80%
See 2 more Smart Citations
“…We attribute the main ones to internal fragments formed by at least two backbone cleavages (see figure 3a). This is in line with our previously reported mass spectra of peptides after X-ray single photon absorption: we showed that peptides of similar size or smaller undergo extensive fragmentation into low-mass ions due to one or two bond cleavages 12,20 .…”
Section: Photoabsorption Mass Spectra Of Peptide Monomerssupporting
confidence: 80%
“…We recently reported such a size effect for a range of peptides and proteins 12 . For soft X-ray photon energies of 150 and 288 eV, we observe the appearance of peaks in the low m/z range which might be due to a high amount of internal energy deposited in [((PPG) 10 ) 3 +7H] 7+ .…”
Section: The ((Ppg) 10 ) 3 Peptide Trimermentioning
confidence: 99%
See 1 more Smart Citation
“…For melittin at room temperature, these channels are known to coexist 16. At T ≈10 K, in contrast, our data show that non‐dissociative single and double ionization become the strongest channels.…”
mentioning
confidence: 57%
“…[15] For melittin at room temperature, these channels are knownt ocoexist. [16] At T % 10 K, in contrast, our data show that non-dissociatives ingle and double ionization become the strongest channels. Figure 1d isplays the experimental data for non-dissociative single ionization (NDSI) of [melittin + qH] q + (q = 2-4).…”
mentioning
confidence: 99%